Identification of African swine fever virus antigens for development of an efficacious subunit vaccine - Zajac, Michelle Dawn (Kansas State University, 2023)
African Swine Fever (ASF) is a virulent disease in domestic swine and wild boar that is caused by the African Swine Fever Virus (ASFV), a complex enveloped DNA virus in the family Asfarviridae. Epidemics caused by the ASFV have an overwhelming economic influence on impacted areas and jeopardize swine commerce globally with nearly 100% mortality in naïve populations. There is no vaccine or treatment available and current control measures focus on the use of antiquated regulatory methods such as quarantine, limiting transport, and depopulation of affected swine. Previous studies have shown that some ASFV mutants can confer protection, but safety and vaccine virus scale-up need to be addressed. Development of a subunit vaccine would be more attractive: however, the actual protective antigen(s) have not yet been identified. The first study aimed to identify ASFV subunit vaccine candidates that contain CD8+ T cell epitopes by using lymphocytes from pigs that had been immunized with an antigen cocktail, which included the largest ASFV protein (pp220 polyprotein) that is processed to generate p5, p34, p14, p37, and p150 individual proteins. The results from this study showed that four predicted SLA-I binding nonamer peptides (p34¹⁶¹ˉ¹⁶⁹, p37⁸⁵⁹ˉ⁸⁶⁷, p150¹³⁶³ˉ¹³⁷¹, and p150¹⁴⁶³ˉ¹⁴⁷¹) elicited robust IFN-[gamma]+ responses in peripheral blood mononuclear cells (PBMCs) and splenocytes. These peptides are highly conserved among different ASFV genomes. The role played by these epitopes in immune protection will need to be determined in challenge studies. In the second study, an adjuvanted or non-adjuvanted adenovirus-based subunit vaccine candidate containing nearly all of the proteins in the ASFV proteome (which included pp220 antigens) was evaluated in pigs in a homologous prime-boost-boost immunization regimen followed by challenge using a natural transmission model. The results of this second study showed that this adenovirus-vectored ASFV vaccine cocktail induced robust antibody responses in swine, but only one pig survived. Future studies will entail the development of a porcine-specific granzyme B (PGB) monoclonal antibody to screen PBMCs from immunized pigs to identify novel IFN-[gamma]+/granzyme B+ T cell epitopes present in ASFV vaccine candidates by using flow cytometric analyses following intracellular staining. More screening is required to identify additional novel IFN-[gamma]+/granzyme B+ T cell epitopes for inclusion in a rationally designed prototype subunit vaccine to be tested for protective efficacy in pigs. Altogether, the knowledge generated in these and future studies will inform the design of an efficacious ASFV subunit vaccine that is needed to safeguard the pork industry against the risk posed by ASFV.
Keywords: African swine fever virus; IgG; IFN-gamma; CTL; SLA-I; Subunit vaccine